Agronomic performance of forage oat genotypes in Santa Catarina western region - Jochims, Felipe (2017)
Abstract – The productivity and cycle of six Creole white oat genotypes, one yellow oat and two commercial cultivars, GUAPA S2 and FAPA II were evaluated. The tests were performed at Epagri/Cepaf area, from 2011 to 2014, in 4m2 experimental sites, with cuts whenever plants reached 30-35 cm in height and keeping 5-8 cm after the cuts. The most productive genotypes were Crioula Iporã do Oeste and Paraíso, with an average of 5 t DM.ha-1, both with long productive cycles. The genotypes Crioula Xanxerê, C. Pesqueiro Xanxerê (white and yellow) and C. Guaraciaba presented an average total production of 3.1 t DM.ha-1 and short cycles, which may be interesting for its use in overgrazing on perennial summer pastures. The cultivar GUAPA S2 presented similar responses to short cycle genotypes and FAPA II and C. Tunápolis presented intermediate and long cycle yields. Oat genotypes with late cycle, present higher biomass production than short cycle genotypes. For overexertion in systems with perennial summer pastures it is recommended the use of early genotypes, with production of concentrated biomass in the first 3 cuts.